PENGARUH PENYULUHAN TERHADAP PENINGKATAN PENGETAHUAN KADER MENGENAI DETEKSI DINI STUNTING - Elviana Prihatiningsih; Rahmi Nurrasyidah; Sugita Sugita; Kuswati Kuswati (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Stunting is still a health problem in Indonesia. The role of cadres is very important in detecting stunting. This study aims to determine the effect of health education on the knowledge of cadres about stunting. This research was conducted in Desa Cangkringan, Kec. Banyudono Kab. Boyolali. The research method is quasi eksperiment with one group pre and post test design. Health education was carried out to all cadres in Desa Cangkringan (26 respondents). Measurement of knowledge was carried out before and after health education using a questionnaire. The results of the study there was an increase in the average value before and after health education, the average value before was 45.9 and after health education was 89.2. The results of the bivariate test showed that there was a relationship between health education and knowledge of cadres about stunting (p value <0.005). The conclusion of this study, health education can increase the knowledge of cadres about stunting.